Gothic documents : a sourcebook 1700-18 - Clery, E. J.; Miles, Robert, 1953- (Manchester University Press, 2017)
How is it that the age of Enlightenment gave rise to the genre of the literary ghost story? What did the term 'Gothic' mean, when Horace Walpole used it in the subtitle of his experimental novel The Castle of Otranto? Based on intensive research, it demonstrates the importance of a historical understanding of the genre, and will be influential in the development of Gothic studies ... It is prestigious and timely: Gothic is a highly active research area and has a growing presence in the university syllabus.. Clery and Miles are well-respected and much cited critics who have already published widely in this field.. This is a unique anthology filling an important gap in the market; an indispensible resource for students, teachers and scholars.
1. Supernaturalism: religion, folklore, Shakespeare 2. Gothic origins 3. The Gothic aesthetic: imagination, originality, terror 4. Anti-Gothic 5. Gothic and revolution 6. Gothic renovations Bibliography.
Keywords: Gothic revival (Literature); Gothic revival (Literature) -- History and criticism.; Horror tales, English.; Horror tales, English -- History and criticism.; Littérature frénétique.; Littérature frénétique -- Histoire et critique.; Récits d'horreur anglais.; Récits d'horreur anglais -- Histoire et critique.; Literature.; Literary Studies -- Fiction, Novelists & Prose Writers.; LITERARY CRITICISM -- General.; Literary studies -- fiction, novelists & prose writers.; Literature -- History & criticism.; LITERARY CRITICISM / General; Anti-Gothic.; Britain.; French Revolution.; Gothic aesthetic: Gothic origins.; Gothic tribes.; Gothic vogue.; cultural theories.; folk tradition.; modern society.; poetry.; primitivism.; sociological theories.; supernatural fiction.; supernaturalism.; Electronic books; Criticism, interpretation, etc.